Comparison of anti‐inflammatory mechanisms of mango (Mangifera Indica L.) and pomegranate (Punica Granatum L.) in a preclinical model of colitis. Issue 9 (23rd May 2016) - Kim, Hyemee; Banerjee, Nivedita; Ivanov, Ivan; Pfent, Catherine M.; Prudhomme, Kalan R.; Bisson, William H.; Dashwood, Roderick H.; Talcott, Stephen T.; Mertens‐Talcott, Susanne U.
Abstract : Mango beverage (rich in gallotannins) inhibits the IGF‐1R‐ AKT/mTOR axis, and pomegranate beverage (rich in ellagitannins) downregulates the mTOR downstream pathway through reduction of ERK1/2 in DSS‐treated rats. Gallic and ellagic acid are predicted in silico to bind to specific targets, such as IGF‐1R and EGFR. Abstract : Scope: Tannin‐rich fruits have been evaluated as alternative prevention strategies for colorectal cancer based on their anti‐inflammatory properties. This study compared tannin‐rich preparations from mango (rich in gallotannins) and pomegranate (rich in ellagitannins) in the dextran sodium sulfate‐induced colitis model. Methods and results: In rats, mango and pomegranate beverages decreased intestinal inflammation and the levels of pro‐inflammatory cytokines in mucosa and serum. The mango beverage suppressed the ratio of phosphorylated/total protein expression of the IGF‐1R‐AKT/mTOR axis and downregulated mRNA expression of Igf1, Insr, and pik3cv . Pomegranate decreased p70S6K and RPS6, as well as Rps6ka2, Map2k2, and Mapk1 mRNA. In silico modeling indicated a high binding of docked of gallic acid to the catalytic domain of IGF‐1R, which may suppress the activity of the enzyme. Ellagic acid docked effectively into the catalytic domains of both IGF‐1R and EGFR. In vitro assays with lipopolysaccharide‐treated CCD‐18Co cells using polyphenolic extracts from each beverage, as well as pure compounds, corroborated the predictions made in silico. Conclusion: Mango polyphenols inhibited the IGF‐1R‐ AKT/mTOR axis, and pomegranate polyphenols downregulate the mTOR downstream pathway through reductions in ERK1/2. These results suggest that extracts rich in gallo‐ and ellagitannins act on different molecular targets in the protection against ulcerative colitis.